Inside the newsroom a case study on the impact of ABS-CBN news Channel's newsroom culture on content - Quinto, Rizza Anne Montaya
"This study was aided by the organizational culture theory of Edgar Schein, the influences to media content theory of Shoemaker and Reese and Hermann and Chomsky's Propaganda Model in determining the impact of ANC's newsroom culture on its content. Focus interviews with ANC's head and employees and immersion in the newsroom were the methods used to obtain data. The study found out that the employees' perceptions and thoughts on ANC's main competencies, brand and its edge over competition and the vision of the founders and heads for the network make up the assumptions, beliefs, and values which are at the core of ANC's newsroom culture. These were manifested in ANC's work environment, team dynamics, physical structures, newsroom policies, practices and norms, employee assessment schemes, network slogans, employees' body language and, or organizational hierarchy. The study pointed out that ANC's culture is grounded on its business objective which is to appeal to its target audience in order to maintain or increase audience share. ANC's target audience are those that belong to the business, diplomatic, political and international sectors including those who are in the topmost economic brackets. The bureaucratic setting and the resulting decision-making hierarchy in the news production workflow enables the target market driven culture to affect ANC's content by ensuring that the heads and employees have the same profit-driven behavior. The study concluded that this type of culture produced a "niching" news production behavior in ANC. This produced content that exclusively caters to its target audience. The study proposed that future researchers explore the culture of print, online and alternative media organizations. It also recommended research methods that would provide a more extensive look into a media organization's culture and initiatives Philippine media organizations should take in order to produce quality journalistic content for the whole citizenry."